Adana İli Arıcılığının Yapısını Belirlemek Üzere Yapılan Bir Anket Çalışması - Mustafa Güneşdoğdu; Ethem Akyol (Turkish Journal of Agriculture: Food Science and Technology, 2019)
Adana province is very suitable for honey bee (Apis mellifera) breeding in terms of climate, geographic structure and rich flora. This study was carried out to investigate of beekeeping structure in Adana. The research was carried out as a questionnaire with technical questions related to technical beekeeping by visiting 169 beekeepers in Adana. In this study, a questionnaire consisting of multiple choice and open-ended questions were used as a data collection method. This survey were obtained data on beekeepers personal information, educational status, reasons for starting beekeeping, how many years they have been beekeeping, recognition of bee diseases and pests, and reared bee species. It is an effort to depict the technical and economic characteristics of province beekeeping practices in order to discover the overall structure of beekeeping in the province. According to the results of the survey, 99.4% of beekeepers’ gender were male, average age 47.77, 58.5% of beekeepers’ education level were primary school, beekeeping experience averaged 19.22 years and colony numbers were 293.21 per beekeeper. Furthermore, the problems of beekeepers were tried to determine.